Manajemen Kinerja Pegawai Pada Badan Amil Zakat Nasional Kabupaten Probolinggo - Achmad Fathor Rosyid; Nur Islamiyah (Cakrawala Repositori IMWI, 2023)
A very crucial mobilizer in the management of institutions is the human resource factor. By good management of human resources, the performance of organizational activity is visible. Performance management is a series of activitiescarried out systematically so that employee performance can be carried out effectively and efficiently. The focus of this research is: (1) How is the management of employee performance in the National Amil Zakat Agency Probolinggo Regency? (2) What are the supporting and inhibiting factors of performance management at National Amil Zakat Agency Probolinggo. The purposes of this study are: (1) To find out employee performance management at National Amil Zakat Agency Probolinggo. (2) To find out the supporting and inhibiting factors of performance management at National Amil Zakat Agency Problinggo. The research method that researcher uses is a descriptive qualitative research method. The data collection is done through observation, interviews, and document review by using purposive technique and triangulation of sourse. The conclusion according to the reasearcher are as follows: (1) Performance management has been carried out by Baznas Probolinggo with planning through RKAT, the realization through appropriate job distribution, evaluation through the annual evaluation forum which is classified into small forums such as evaluation every 3 months and specified again into once a month. (2) Inhibiting factors for technical and lack of discipline of employees. As well as supporting factors, good communication is build.